Aesthetic experiences and classical antiquity the significance of form in narratives and pictures - Grethlein, Jonas 1978- (Cambridge University Press, 2017)
"In this bold book, Jonas Grethlein proposes a new dialogue between the fields of Classics and aesthetics. Ancient material, he argues, has the capacity to challenge and re-orientate current debates. Comparisons with modern art and literature help to balance the historicism of classical scholarship with transcultural theoretical critique. Grethlein discusses ancient narratives and pictures in order to explore the nature of aesthetic experience. While our responses to both narratives and pictures are vicarious, the 'as-if' on which they are premised is specifically shaped by the form of the representation. Form emerges as a key to how narratives and pictures constitute an important means of engaging with experience. Combining theoretical reflections with close readings, this book will appeal to textual scholars as well as to art historians"...
Includes bibliographical references and index
Keywords: HISTORY / Ancient / General / bisacsh; Aesthetics, Ancient; Arts, Classical -- Philosophy; Classical antiquities in art; Classical literature -- History and criticism; Classical antiquities in literature; HISTORY / Ancient / General; Ästhetik; Literatur; Kunst; Antike